We know the formula of Bezier spline is:

x=A1*t*t*t+3*B1*t*t+3*C1*t+X0

y=A2*t*t*t+3*B2*t*t+3*C2*t+Y0

But I want to know how can I get the “y” value from “x”,I’m searching a bezier spline formula like y=f(x),is it possible?

We know the formula of Bezier spline is:

x=A1*t*t*t+3*B1*t*t+3*C1*t+X0

y=A2*t*t*t+3*B2*t*t+3*C2*t+Y0

But I want to know how can I get the “y” value from “x”,I’m searching a bezier spline formula like y=f(x),is it possible?

Originally posted by pango:

[b]We know the formula of Bezier spline is:

x=A1ttt+3B1tt+3C1t+X0

y=A2ttt+3B2tt+3C2t+Y0

But I want to know how can I get the “y” value from “x”,I’m searching a bezier spline formula like y=f(x),is it possible?[/b]

The functions you use are called parametric equations. If you want the canonic form, you’ll have to do some maths.

Reduce one of them for t, then replace the calculated value of t inside the other function. This will be very hard (and maybe not really possible) because you have powers of t. Thus you’ll end with several possibilities for the second calculations.

So my advice is not to use y=f(x) but stay with those parametric formulations.

Hope that helps.